Fields of training, plant characteristics and the gender wage gap in entry wages among skilled workers: evidence from German administrative data - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
This paper investigates the gender wage gap among skilled German workers after the end of vocational training using data from social security record. Using information on worker and plant characteristics for both the training plant and the current employer, results from standard decomposition techniques show that up to 91% of an initial 14% earnings disadvantage for women in the first job can be attributed to differences in endowments. Of these, occupational segegreation explains up to two thirds of the earnings gap, with plant characteristics accounting for up to 30%.
Keywords: J24; J31; J71; 330; Gender wage gap; decomposition; field of training; Lohndifferenzierung; Geschlechterdiskriminierung; Berufsausbildung; Facharbeiter; Berufseinstieg; Erwerbsverlauf; Berufswahl; Dekompositionsverfahren; Deutschland